Women’s adornment and hairstyle tools from Jerash archaeological site/ Jordan - Shiyyab, Adnan; Abuhelaleh, Bellal (Dirasat: Human and Social Sciences, 2021)
During the Roman period, women fashion was of special value, and was afforded special care during daily life and important ceremonials. Hair and face treatments reflected many particular issues such as imperial position, wealth and even individual beauty for local women. Our paper presents a variety of ivory and bone artifacts recovered during the excavations of the northern part of Jerash during the 2018 and 2019 seasons. 20 artifacts made of ivory and bone material, were found in Roman occupation strata. The artifacts are women’s tools used with adornments and hairstyles during the Roman period. It also presents a rare case of documenting red pigments on different artifacts. This study includes the classification of these artifacts and their uses during the Roman period in Jerash site, especially in the area of excavations.